Mixture and solar cell

By using a mixture of silicon sol dispersion, mesoporous oxides and phosphate or amine additives in solar cells to form a film layer, the problem of potential-induced attenuation in photovoltaic modules is solved, and the power generation efficiency and anti-attenuation performance are improved.

CN119119781APending Publication Date: 2024-12-13TRINA SOLAR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411236095.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

There is a potential-induced attenuation effect caused by potential difference in photovoltaic modules, which leads to power attenuation of photovoltaic modules. The prior art is difficult to effectively reduce this problem.

Method used

Using a mixture, including silica sol dispersion, mesoporous oxides and phosphates or amine additives, the precipitation and migration of positively charged ions are prevented by forming a film layer on the surface of the middle layer structure of the solar cell, including phosphates. The mass ratio of additives and mesoporous oxides is 1:0.2-200, the mass ratio of amine additives and mesoporous oxides is 1:0.2-200, the particle size of mesoporous oxides is 30-50nm, and the silica sol dispersion is Preparation method and coating method.

Benefits of technology

It effectively reduces the potential-induced attenuation in photovoltaic modules, improves the power generation efficiency of solar cells, and enhances the potential-induced attenuation performance by preventing the migration and precipitation of metal cations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119781A_ABST
    Figure CN119119781A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a mixture and a solar cell. Wherein the mixture comprises silica sol dispersion liquid, mesoporous oxide and phosphate additives and / or amine additives. Wherein the mass ratio of the phosphate additive to the mesoporous oxide is 1: (0.2-200), and / or the mass ratio of the amine additive to the mesoporous oxide is 1: (0.2-200). According to the mixture provided by the embodiment of the invention, the surface of the middle layer structure of the solar cell can be coated with the mixture to form a film layer. The film layer can reduce precipitation of positive charge ions and / or prevent the positive charge ions from moving towards the interior of the battery piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of photovoltaic cells, and in particular to a mixture and a solar cell. Background Art

[0002] In a photovoltaic module, there is a potential difference between the circuit inside the module and the metal frame surrounding the module, which results in an electric field from outside to inside between the battery inside the module and the external metal frame. Under the action of the electric field force, positively charged ions move and diffuse from the surface of the battery toward the PN junction inside the battery, causing the power of the photovoltaic module to decay. This phenomenon is the PID (Potential Induced Degradation) effect.

[0003] How to reduce the PID of photovoltaic modules has become a technical problem that needs to be solved urgently in the field of photovoltaic cell technology.

[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention

[0005] The embodiments of the present application provide a mixture and a solar cell to solve or alleviate one or more of the technical problems mentioned above.

[0006] In a first aspect of an embodiment of the present application, a mixture is provided, comprising: a silica sol dispersion, a mesoporous oxide, and a phosphate additive and / or an amine additive; wherein:

[0007] The mass ratio of the phosphate additive to the mesoporous oxide is 1:0.2-200, and / or the mass ratio of the amine additive to the mesoporous oxide is 1:0.2-200.

[0008] In one embodiment, the mixture includes a phosphate-based additive and an amine-based additive.

[0009] In one embodiment, the phosphate additive includes one or more of aluminum phosphate, titanium phosphate and zinc phosphate.

[0010] In one embodiment, the particle size of the mesoporous oxide is 30-50 nm.

[0011] In one embodiment, the mesoporous oxide is mesoporous silica.

[0012] In one embodiment, the silica sol dispersion is prepared by the following method:

[0013] Add ethyl silicate to anhydrous ethanol and stir until the mixture is uniform;

[0014] Add hexamethyldisilazane dropwise and stir until well mixed;

[0015] Add deionized water and stir for 2-3 hours to form silica sol;

[0016] The silica sol is aged for a preset time under a preset aging environment to obtain a silica sol dispersion; wherein the volume ratio of ethyl silicate, hexamethyldisilazane, deionized water and anhydrous ethanol is 0.002-5:0.002-5:0.002-5:1.

[0017] According to a second aspect of an embodiment of the present application, a solar cell is provided, comprising: a cell body, a packaging film, a packaging glass and a barrier layer; the packaging glass is located on the surface of the solar cell, and the packaging film is located between the cell body and the packaging glass; the barrier layer is located on the side of the packaging glass close to the cell body, and on the side of the packaging film facing the packaging glass; the barrier layer is made of a mixture of any of the above-mentioned embodiments.

[0018] In one embodiment, the barrier layer is prepared by coating the mixture on the surface of the encapsulation glass in a sol-gel, magnetron sputtering or evaporation manner; the thickness of the prepared barrier layer is 100-300 nm.

[0019] In one embodiment, the encapsulation film includes: an anti-aging aid and an acid absorbent;

[0020] The anti-aging aid includes one or more of phenolic antioxidants, phosphite antioxidants, hindered amine light stabilizers and ultraviolet cut-off agents;

[0021] The acid scavenger includes one or more of triethylamine, triethylenediamine, DBU, DBN, DMAP, pyridine, N-methylmorpholine and tetramethylethylenediamine.

[0022] In one embodiment, the packaging film includes a first packaging film and a second packaging film; the first packaging film is arranged close to the battery cell body, and the second packaging film is located on a side of the first packaging film away from the battery cell body;

[0023] The first packaging film also includes an ion capture agent and an anti-hydrolysis agent; the ion capture agent includes one or more of aluminum phosphate, titanium phosphate and zinc phosphate; the anti-hydrolysis agent includes one or more of butyl acrylate, hydroxyethyl acrylate, ethyl methacrylate and hydroxyethyl methacrylate.

[0024] In one embodiment, the thickness of the first packaging film is 1 / 10-1 / 3 of the thickness of the second packaging film.

[0025] The embodiment of the present application adopts the above technical solution and may include the following advantages: by coating the mixture on the surface of the middle layer structure of the solar cell to form a film layer. The mixture may be coated on the inner side or outer side of the encapsulation glass, or on the inner side of the encapsulation film, to reduce the precipitation of positively charged ions and / or prevent the positively charged ions from moving toward the inside of the cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.

[0027] Figure 1 A schematic diagram of the stacked structure of a solar cell provided in an embodiment of the present application is shown. DETAILED DESCRIPTION

[0028] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.

[0029] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. And when the second element, component, region, layer or part is discussed, it does not mean that the present disclosure necessarily has the first element, component, region, layer or part.

[0030] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0031] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0032] Hereinafter, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. It should be noted that these exemplary embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.

[0033] In solar cells, the power generation efficiency of solar cells will decay due to the potential induced degradation (PID) effect; therefore, reducing the potential induced degradation in solar cells can improve the power generation efficiency of solar cells. Reducing the potential induced degradation in solar cells can serve as a breakthrough to further improve the power generation efficiency of solar cells.

[0034] In photovoltaic modules, the encapsulation film undergoes oxidation and hydrolysis as the photovoltaic modules are used, resulting in aging. Encapsulation films, such as EVA (Polyethylene vinylacetate) films, produce acetic acid after aging, which reacts with Na2CO3 in the encapsulation glass (soda-lime glass) to precipitate Na + , Ca +2Ions. Furthermore, the metal frame of the photovoltaic module is grounded, and the solar cells in the photovoltaic module are connected in series to form a battery string to increase the system voltage and reduce the cost and loss of power transmission; this method will cause a potential difference between the internal circuit in the photovoltaic module and the metal frame, forming an electric field from the outside to the inside; under the action of the electric field force, the positively charged ions precipitated in the packaging material (packaging film and packaging glass) move toward the direction of the battery cell, causing the power attenuation of the photovoltaic module.

[0035] The present application provides a mixture, comprising: a silica sol dispersion, a mesoporous oxide, and a phosphate additive and / or an amine additive, wherein the mass ratio of the phosphate additive to the mesoporous oxide is 1:0.2-200, and / or the mass ratio of the amine additive to the mesoporous oxide is 1:0.2-200.

[0036] In some embodiments, the mass ratio of the phosphate additive to the mesoporous oxide can be: 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190, 1:200, etc.

[0037] In other embodiments, the mass ratio of the amine additive to the mesoporous oxide can be: 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190, 1:200, etc.

[0038] In an embodiment of the present application, the silica sol dispersion can be used as a solvent to dissolve or mix the mesoporous oxide and the phosphate additives and / or the amine additives, so that the formed mixture can include the mesoporous oxide and the phosphate additives and / or the amine additives, and the mixture can be coated on the surface of the middle layer structure of the solar cell to form a film layer.

[0039] The interior of the mesoporous oxide includes abundant internal surface active sites, which, in combination with phosphate additives and / or amine additives, enable the mesoporous oxide to have the ability to capture metal cations and neutralize acetic acid.

[0040] The phosphate additives in the mixture can capture metal cations, thereby preventing the migration of metal cations and preventing the metal cations from moving toward the inside of the battery cell.

[0041] The amine additive in the mixture is an alkaline additive, which can neutralize acetic acid, that is, reduce the content of acetic acid inside the battery, thereby reducing the precipitation of metal cations, that is, reducing the metal cations migrating toward the interior of the battery cell.

[0042] The mixture can include phosphate additives and amine additives at the same time, that is, it can reduce the metal cations migrating into the battery cell from two aspects, such as preventing the migration of metal cations and reducing the precipitation of metal cations, thereby reducing potential induced decay from multiple angles and improving the power generation efficiency of solar cells.

[0043] In some specific application scenarios, the mixture may include one of the phosphate additives and the amine additives. Such a solution can also reduce the potential induced degradation of the solar cell.

[0044] The present application provides a mixture, which can be applied to the surface of the middle layer structure of the solar cell to form a film layer. The mixture can be applied to the inner side or outer side of the encapsulation glass, or the inner side of the encapsulation film, to reduce the precipitation of positively charged ions and / or prevent the positively charged ions from moving toward the inside of the cell.

[0045] In one example, the mixture provided in the embodiment of the present application is used to coat the inner side of the encapsulation glass, which can prevent the contact between the encapsulation film and the encapsulation glass, thereby further preventing the acetic acid generated by the encapsulation film from reacting with the encapsulation glass, and preventing Na + The precipitation of ions further improves the potential induced degradation performance of solar cells.

[0046] In one embodiment, the mixture includes a phosphate-based additive and an amine-based additive.

[0047] In the embodiment of the present application, a solution is adopted in which a phosphate additive and an amine additive are included in the mixture. By using the mixture and adding a film layer made of the mixture to a solar cell, the metal cations migrating toward the inside of the cell can be reduced from two aspects, namely, preventing the migration of metal cations and reducing the precipitation of metal cations, thereby reducing potential induced decay from multiple angles and improving the power generation efficiency of the solar cell.

[0048] Based on the joint action of phosphate additives and amine additives, they can also produce a mutually reinforcing effect in preventing the migration of metal cations and reducing the precipitation of metal cations, thereby achieving an effect of 1+1>2.

[0049] In one embodiment, the phosphate additive includes one or more of aluminum phosphate, titanium phosphate, and zinc phosphate. Phosphate additives are used to capture metal cations, especially Na+ Ions, sodium ions account for 13%-14% of the packaging glass. Therefore, phosphate additives are used to capture Na + Ions can reduce the number of free metal cations, thereby preventing the metal cations from migrating into the battery cell.

[0050] In one embodiment, the particle size of the mesoporous oxide is 30-50 nm.

[0051] Mesoporous oxides refer to oxides with a mesoporous structure. Mesopores refer to pores with a pore size of 2-50 nm.

[0052] The mesoporous oxide has a hollow pore structure, a high specific surface area and good catalytic performance. It can adsorb phosphate additives and / or amine additives well, and can catalyze their capture effect or neutralize acetic acid.

[0053] The particle size of the mesoporous oxide is 30-50nm, and the thickness of the film layer including the mesoporous oxide is above 60nm, so that the film layer including the mesoporous oxide can have multiple layers of mesoporous oxide particles, and the film layer can be fully covered without gaps to prevent the migration of metal cations as much as possible. Therefore, by limiting the particle size of the mesoporous oxide to 30-50nm, the mesoporous oxide in the film layer can be fully covered without gaps in the case of a thin film layer, so as to prevent metal cations as much as possible and ensure the anti-potential induced decay effect.

[0054] Illustratively, the particle size of the mesoporous oxide may be, for example, 30 nm, 35 nm, 45 nm, or 50 nm.

[0055] In one embodiment, the mesoporous oxide is mesoporous silica.

[0056] Mesoporous silica has a similar refractive index to the silica of the encapsulation glass, and has a smaller impact on the light transmittance of the entire encapsulation material. Therefore, mesoporous silica is a preferred solution for the mesoporous oxide.

[0057] In addition, mesoporous silica has an ordered pore structure, which can further improve the transmittance of light.

[0058] In one embodiment, the silica sol dispersion is prepared by the following method:

[0059] Add ethyl silicate to anhydrous ethanol and stir until the mixture is uniform;

[0060] Add hexamethyldisilazane dropwise and stir until well mixed;

[0061] Add deionized water and stir for 2-3 hours to form silica sol;

[0062] The silica sol is aged for a preset time under a preset aging environment to obtain a silica sol dispersion; wherein the volume ratio of ethyl silicate, hexamethyldisilazane, deionized water and anhydrous ethanol is 0.002-5:0.002-5:0.002-5:1.

[0063] By preparing the silica sol dispersion in the above manner, modified silane can be obtained, and the modified silane can improve the polymerization performance of the mesoporous oxide, phosphate additives and / or amine additives, and further improve the comprehensive performance of the mixture.

[0064] The silica sol dispersion prepared in the embodiment of the present application can dissolve or mix the mesoporous oxide, phosphate additives and / or amine additives, and make the mixed mixture have the property of being coated on the surface of the structure to form a film layer.

[0065] In one example, it can be: take 10 mL of ethyl silicate and add it to 100 mL of anhydrous ethanol, mix and stir evenly; then slowly add 10 mL of hexamethyldisilazane, mix and stir for 30 minutes until it is evenly mixed; then drop 11 mL of deionized water into the above mixture, stir for 2 hours to form a transparent silica sol, and store it in a sealed container; then age the above transparent silica sol for 10 days to obtain a silica sol dispersion.

[0066] The present application also provides a solar cell, such as Figure 1 As shown, it includes: a battery cell body 100, a packaging film, a packaging glass 400 and a barrier layer 300; the packaging glass 400 is located on the surface of the solar cell, and the packaging film is located between the battery cell body 100 and the packaging glass 400; the barrier layer 300 is located on the side of the packaging glass 400 close to the battery cell body 100, and on the side of the packaging film facing the packaging glass 400; the barrier layer 300 is made of a mixture of any implementation aspect of the above-mentioned embodiments.

[0067] In one example, a packaging film, a barrier layer 300 and a packaging glass 400 are stacked in sequence on the front side of the battery cell body 100; at the same time, a packaging film, a barrier layer 300 and a packaging glass 400 are stacked in sequence on the back side of the battery cell body 100; so that the potential induction on the front side and / or the back side of the battery cell body 100 can be reduced at the same time; and metal cations are prevented from moving from the front side and / or the back side of the battery cell body 100 toward the battery cell body 100.

[0068] In one example, the cell body 100 is an N-type cell. Since the front PID effect of the N-type cell is greater than the back PID effect, the thickness of the barrier layer 300 located on the front side of the cell body 100 can be set to be greater than the thickness of the barrier layer 300 on the back side of the cell body 100, so as to reduce potential induced decay and improve the power generation efficiency of the solar cell while saving costs and reducing the thickness of the solar cell.

[0069] In one embodiment, the barrier layer 300 is prepared by coating the mixture on the surface of the encapsulation glass 400 by sol-gel, magnetron sputtering or evaporation; the thickness of the barrier layer 300 is 100-300 nm.

[0070] The barrier layer 300 is a film layer made of the mixture provided in the embodiment of the present application. The mixture needs to be coated on the surface of the encapsulation glass 400. Any method that can evenly coat the mixture on the surface of the encapsulation glass 400 can be used, for example, sol-gel, magnetron sputtering or evaporation methods can be used.

[0071] The thickness of the barrier layer 300 can be determined based on the amount of mesoporous oxide to be coated; further, it can be determined based on the metal cation content of the encapsulating glass 400; further, it can be determined based on the aging degree of the encapsulating film or the production of acetic acid during the aging process; it can be understood that it can also be determined based on one or more of the aforementioned amount of mesoporous oxide to be coated, the metal cation content of the encapsulating glass 400 and the aging degree of the encapsulating film.

[0072] In one example, the amount of silica sol dispersion can be determined according to the thickness of the barrier layer 300 to be coated, and the amount of mesoporous oxide to be added to the mixture can be determined according to the amount of mesoporous oxide to be coated, and the amount of phosphate additives and / or amine additives in the mixture can be further determined. The aforementioned "amount" can be volume or mass, depending on the actual situation.

[0073] Based on the law of refraction of light and the inventor's multiple experimental test experience, the thickness of the barrier layer 300 is limited to 100-300nm. Within this thickness range, the transmittance of the encapsulation glass 400 is slightly affected, which can meet the effect of reducing the resistance of solar cells to potential induced degradation.

[0074] In one example, when better resistance to potential induced degradation is required, the thickness of the barrier layer 300 may be set to be thicker, for example, 300 nm.

[0075] In one example, based on comprehensive considerations of potential induced degradation resistance and thickness of solar cells, the thickness of the barrier layer 300 may be set to, for example, 100 nm, 150 nm, 200 nm, or 250 nm.

[0076] In one example, when the particle size of the mesoporous oxide is smaller, for example, when the average particle size is close to 30 nm, the thickness of the barrier layer 300 can be set to 100 nm.

[0077] In one embodiment, the encapsulating film includes: an anti-aging agent and an acid absorber; the anti-aging agent includes one or more of a phenolic antioxidant, a phosphite antioxidant, a hindered amine light stabilizer and a UV cutoff agent; the acid absorber includes one or more of triethylamine, triethylenediamine, DBU (bicyclic amidine, 1,8-diazabicyclo (5,4,0)-7-undecene), DBN (1,5-diazabicyclo [4.3.0] -5-nonene), DMAP (4-dimethylaminopyridine), pyridine, N-methylmorpholine and tetramethylethylenediamine.

[0078] The anti-aging agent is used to improve the anti-aging performance of the packaging film and reduce the acetic acid generated by the packaging film due to aging. The acid absorber is an alkaline additive used to absorb and neutralize the acetic acid generated in the packaging film.

[0079] In one embodiment, the encapsulation film includes a first encapsulation film 210 and a second encapsulation film 220; the first encapsulation film 210 is arranged close to the battery cell body 100, and the second encapsulation film 220 is located on the side of the first encapsulation film 210 away from the battery cell body 100; the first encapsulation film 210 also includes an ion capture agent and an anti-hydrolysis agent; the ion capture agent includes one or more of aluminum phosphate, titanium phosphate and zinc phosphate; the anti-hydrolysis agent includes one or more of butyl acrylate, hydroxyethyl acrylate, ethyl methacrylate and hydroxyethyl methacrylate.

[0080] Ion capture agents are used to capture metal cations and reduce the migration of metal cations.

[0081] In one embodiment, the thickness of the first packaging film 210 is 1 / 10-1 / 3 of the thickness of the second packaging film 220 .

[0082] The first packaging film 210 is close to the cell body 100, and contains an ion capture agent and an anti-hydrolysis agent, which has better anti-PID performance and can prevent metal cations from moving toward the cell body 100. The second packaging film 220 plays the role of bonding and packaging, and the anti-aging additive and acid absorbent contained in it can delay its aging, that is, reduce the effect of acetic acid produced by it, without affecting the packaging effect.

[0083] In the embodiment of the present application, the packaging film adopts a double-layer structure, and the first packaging film 210 close to the battery cell body 100 has a stronger anti-PID performance, so that the anti-PID performance of the entire solar cell can be enhanced. At the same time, by only enhancing the anti-PID performance of the first packaging film 210, the cost of the packaging film can be saved while ensuring the anti-PID performance.

[0084] The embodiment of the present application adds an anti-aging agent and an acid absorber to the packaging film to delay the aging of the packaging film and reduce the acetic acid content generated, thereby improving its anti-PID performance. In order to further improve the anti-PID performance of the packaging film, an ion capture agent and an anti-hydrolysis agent are added to the first packaging film 210 close to the battery cell body 100 to further reduce the potential induced decay effect. At the same time, by adding the ion capture agent and the anti-hydrolysis agent separately to the first packaging film 210, the usage of the ion capture agent and the anti-hydrolysis agent can be reduced, thereby reducing the cost of the packaging film.

[0085] In solar cells, the thickness of the encapsulation film can be 100-500 μm.

[0086] In one example, based on the sum of the thickness of the first packaging film 210 and the thickness of the second packaging film 220 , that is, the thickness of the packaging film, the thickness of the first packaging film 210 for obtaining the best anti-PID performance is determined, and then the thickness of the second packaging film 220 is determined.

[0087] The encapsulation film in the embodiment of the present application can be obtained by first obtaining the master batch of the first encapsulation film 210 and the master batch of the second encapsulation film 220, and then casting the master batch of the first encapsulation film 210 and the master batch of the second encapsulation film 220 into films through a double-layer co-extrusion die. The master batch of the first encapsulation film 210 and the master batch of the second encapsulation film 220 are respectively fed into the two feeding ports of the double-layer co-extrusion die, and the thickness of the first encapsulation film 210 and the thickness of the second encapsulation film 220 are set by adjusting the parameters of the double-layer co-extrusion die.

[0088] In the embodiment of the present application, by limiting the ratio of the thickness of the first packaging film 210 to the thickness of the second packaging film 220, the thickness of the first packaging film 210 can be determined while comprehensively satisfying the requirements of anti-PID performance and the cost of the packaging film.

[0089] In one example, the thickness of the first packaging film 210 may be 30-100 μm; the thickness of the second packaging film 220 may be 100-400 μm.

[0090] In the solar cell, the thickness of the first encapsulation film 210 on the front side of the cell body 100 may be different from the thickness of the first encapsulation film 210 on the back side of the cell body 100. Similarly, the thickness of the second encapsulation film 220 on the front side of the cell body 100 may be different from the thickness of the second encapsulation film 220 on the back side of the cell body 100.

[0091] In one example, the cell body 100 is an N-type cell. Since the front PID effect of the N-type cell is greater than the back PID effect, the thickness of the first packaging film 210 located on the front of the cell body 100 can be set to be greater than the thickness of the first packaging film 210 on the back of the cell body 100, so as to reduce potential induced decay and improve the power generation efficiency of the solar cell, while also saving costs and reducing the thickness of the solar cell.

[0092] In one example, the cell body 100 is an IBC (interdigitated back contact) cell, which has no grid lines on the front and the welding lines are all on the back of the cell. The thickness of the first adhesive film on the back of the cell body 100 can be set to 1 / 10 of the thickness of the second adhesive film, or can be 0 in some necessary scenarios; further, the thickness of the barrier layer 300 on the front of the cell body 100 can be set to 0μm.

[0093] The following will conduct performance tests on the structure or manufacturing method of the solar cell provided in the embodiments of the present application and related comparative examples.

[0094] [Example 1]

[0095] Take 10 mL of ethyl silicate and add it to 20 mL of anhydrous ethanol, mix and stir evenly, then slowly add 10 mL of hexamethyldisilazane, mix and stir for 30 minutes until mixed evenly, then drop 50 mL of deionized water into the above mixture, stir for 2 hours to form a silica sol, and seal for storage; then place the above silica sol at room temperature for 10 days to age the silica sol to obtain a silica sol dispersion.

[0096] 0.5 g of mesoporous silica nanoparticles with a particle size of 40 nm, 0.12 g of aluminum phosphate and 0.2 g of triethylamine were added to the silica sol dispersion and stirred until completely mixed to obtain a mixture A.

[0097] The mixture A was applied to the inner surface of an ultra-white semi-tempered embossed glass having a thickness of 2.0 mm by roller coating to a thickness of 100 nm to form a barrier layer on the inner surface of the ultra-white semi-tempered embossed glass.

[0098] Weigh 0.5 parts of phosphite antioxidant and hindered amine light stabilizer in a mass ratio of 1:1, 0.5 parts of titanium phosphate as an ion scavenger, 0.5 parts of triethylenediamine as an acid absorber, and 0.1 parts of butyl acrylate, stir and mix at room temperature, and control the stirring speed to 50 rpm to ensure that there is no adhesion during the stirring of the auxiliary agents. After stirring evenly, add 0.3 parts of the main cross-linking agent, 0.1 parts of the auxiliary cross-linking agent, and 0.3 parts of the silane coupling agent, continue stirring to ensure that the materials are evenly mixed; finally, add 100 parts of EVA resin and mix to obtain material A of the first encapsulation film.

[0099] Weigh 0.5 parts of phosphite antioxidant and hindered amine light stabilizer in a mass ratio of 1:1, and 0.5 parts of triethylenediamine as an acid absorber, stir and mix at room temperature, control the stirring speed to 50 rpm, and ensure that there is no adhesion during the stirring of the additives. After stirring evenly, add 0.3 parts of the main cross-linking agent, 0.1 parts of the auxiliary cross-linking agent, and 0.3 parts of the silane coupling agent, continue stirring to ensure that the materials are evenly mixed; finally, add 100 parts of EVA resin and mix to obtain material B of the second encapsulation film.

[0100] Add material A and material B into the double-layer co-extrusion die head according to preset proportions to obtain a front film with a first encapsulation film thickness of 70 μm and a second encapsulation film thickness of 210 μm; and a back film with a first encapsulation film thickness of 50 μm and a second encapsulation film thickness of 350 μm.

[0101] according to Figure 1 The structure shown is stacked in sequence, with the front film stacked on the front of the cell body and the back film stacked on the back of the cell body. The thickness of the barrier layer on the front and back of the cell body is the same, as is the thickness of the encapsulation glass on the front and back of the cell body.

[0102] [Example 2]

[0103] The only difference from Example 1 is that after obtaining the silica sol dispersion, 0.5 g of mesoporous silica nanoparticles with a particle size of 40 nm, 0.3 g of aluminum phosphate and 0.3 g of triethylamine are added to the silica sol dispersion and stirred until completely mixed to obtain a mixture B.

[0104] The mixture B was coated on the inner surface of 2.0 mm thick ultra-white semi-tempered embossed glass by roller coating to a thickness of 100 nm.

[0105] [Example 3]

[0106] The only difference from Embodiment 1 is that the material composition of the first packaging film and the second packaging film is different.

[0107] Material C of the first packaging film: weigh 0.5 parts of phosphite antioxidant and hindered amine light stabilizer, the mass ratio of the two is 1:1, 0.1 parts of titanium phosphate as an ion capture agent, 0.25 parts of triethylenediamine acid absorber, 0.05 parts of butyl acrylate, stir and mix at room temperature, control the stirring speed to 50 rpm, and ensure that there is no adhesion during the stirring of the auxiliary agents. After stirring evenly, add 0.3 parts of the main cross-linking agent, 0.1 parts of the auxiliary cross-linking agent, and 0.3 parts of the silane coupling agent, continue stirring to ensure that the materials are evenly mixed; finally, add 100 parts of EVA resin for mixing.

[0108] Material D of the second encapsulation film: Weigh 0.5 parts of phosphite antioxidant and hindered amine light stabilizer, with a mass ratio of 1:1, and 0.25 parts of triethylene diamine acid absorber, stir and mix at room temperature, control the stirring speed to 50 rpm, and ensure that there is no adhesion during the stirring of the auxiliary agents. After stirring evenly, add 0.3 parts of the main cross-linking agent, 0.1 parts of the auxiliary cross-linking agent, and 0.3 parts of the silane coupling agent, continue stirring to ensure that the materials are mixed evenly; finally, add 100 parts of EVA resin and mix.

[0109] Add material C and material D into the double-layer co-extrusion die head according to preset proportions to obtain a front film with a first encapsulation film thickness of 70 μm and a second encapsulation film thickness of 210 μm; and a back film with a first encapsulation film thickness of 50 μm and a second encapsulation film thickness of 350 μm.

[0110] [Comparative Example 1]

[0111] The only difference from Example 1 is that the solar cell structure does not include a barrier layer.

[0112] [Comparative Example 2]

[0113] The only difference from Example 1 is that the front and back packaging films each have only one layer and are made of material B. The thickness of the front film is 70+210=280 μm; the thickness of the back film is 50+350=400 μm.

[0114] [Comparative Example 3]

[0115] The only difference from Example 1 is that the solar cell structure does not include a barrier layer, and the front and back packaging films each have only one layer and are made of material B. The thickness of the front film is 70+210=280μm; the thickness of the back film is 50+350=400μm.

[0116] The solar cells prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to PID performance tests respectively. The test conditions were -1500 V, temperature 85° C., humidity 85 RH%, and the test time was 96 h and 192 h respectively.

[0117] The test results are shown in Table 1:

[0118] Table 1. PID performance test results of solar cells prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0119]

[0120] Based on the data in Table 1, it can be seen that the anti-PID effect in Example 2 is not much different from that in Example 1, so the added aluminum phosphate and triethylamine mainly affect the light transmittance of the glass, and when the added amount of aluminum phosphate is 0.12g, the capture of free sodium ions can meet the requirements.

[0121] Based on the data in Table 1, it can be seen that in Example 3, the barrier layer is the same as that in Example 1, but the formulas of the first encapsulation film and the second encapsulation film are slightly adjusted, which slightly affects the anti-PID performance.

[0122] Based on the data in Table 1, it can be seen that in the case where Comparative Example 1 does not include a barrier layer, even if the encapsulation film includes sufficient ion capture agents and anti-hydrolysis agents, the anti-PID performance is weak.

[0123] Based on the data in Table 1, it can be seen that when Comparative Example 2 includes a barrier layer but the encapsulation film does not include an ion capture agent and an anti-hydrolysis agent, the anti-PID performance is weak, but better than Comparative Example 1.

[0124] Based on the data in Table 1, it can be seen that Comparative Example 3 does not include a barrier layer and uses an encapsulation film without an ion scavenger, and has poor anti-PID performance.

[0125] It should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The orientation words "inside" and "outside" refer to the inside and outside relative to the outline of each component itself. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Therefore, the exemplary term "above..." can include both "above..." and "below..." orientations. The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here are interpreted accordingly.

[0126] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when a specific feature, structure or characteristic is described in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.

[0127] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0128] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A mixture, characterized in that include: Silica sol dispersion, mesoporous oxide and phosphate additives and / or amine additives; wherein, The mass ratio of the phosphate additive to the mesoporous oxide is 1:0.2-200, and / or the mass ratio of the amine additive to the mesoporous oxide is 1:0.2-200.

2. The mixture according to claim 1, characterized in that The mixture includes the phosphate additive and the amine additive.

3. The mixture according to claim 1 or 2, characterized in that The phosphate additive includes one or more of aluminum phosphate, titanium phosphate and zinc phosphate.

4. The mixture according to claim 1 or 2, characterized in that The particle size of the mesoporous oxide is 30-50 nm.

5. The mixture according to claim 1 or 2, characterized in that The mesoporous oxide is mesoporous silica.

6. The mixture according to claim 1, characterized in that The silica sol dispersion is prepared by the following method: Add ethyl silicate to anhydrous ethanol and stir until the mixture is uniform; Add hexamethyldisilazane dropwise and stir until well mixed; Add deionized water and stir for 2-3 hours to form silica sol; The silica sol is aged for a preset time under a preset aging environment to obtain the silica sol dispersion; wherein the volume ratio of the ethyl silicate, the hexamethyldisilazane, the deionized water and the anhydrous ethanol is 0.002-5:0.002-5:0.002-5:

1.

7. A solar cell, characterized in that: include: Cell body, encapsulation film, encapsulation glass and barrier layer; The encapsulation glass is located on the surface of the solar cell, and the encapsulation film is located between the cell body and the encapsulation glass; The barrier layer is located on a side of the encapsulation glass close to the battery cell body, and is located on a side of the encapsulation film facing the encapsulation glass; the barrier layer is made of the mixture according to any one of claims 1 to 6.

8. The solar cell according to claim 7, characterized in that: The barrier layer is prepared by coating the mixture on the surface of the encapsulation glass in a sol-gel, magnetron sputtering or evaporation manner; the thickness of the barrier layer is 100-300 nm.

9. The solar cell according to claim 7, characterized in that: The packaging film comprises: an anti-aging aid and an acid absorbent; The anti-aging aid includes one or more of phenolic antioxidants, phosphite antioxidants, hindered amine light stabilizers and ultraviolet cut-off agents; The acid scavenger includes one or more of triethylamine, triethylenediamine, DBU, DBN, DMAP, pyridine, N-methylmorpholine and tetramethylethylenediamine.

10. The solar cell according to claim 7 or 9, characterized in that: The packaging film comprises a first packaging film and a second packaging film; the first packaging film is arranged close to the battery cell body, and the second packaging film is located on a side of the first packaging film away from the battery cell body; The first packaging film also includes an ion capture agent and an anti-hydrolysis agent; the ion capture agent includes one or more of aluminum phosphate, titanium phosphate and zinc phosphate; the anti-hydrolysis agent includes one or more of butyl acrylate, hydroxyethyl acrylate, ethyl methacrylate and hydroxyethyl methacrylate.

11. The solar cell according to claim 10, characterized in that: The thickness of the first packaging film is 1 / 10-1 / 3 of the thickness of the second packaging film.

Citation Information

Patent Citations

  • Multi-layer composite photovoltaic packaging adhesive film resistant to PID (potential induced degradation) as well as preparation method and application

    CN109337599A

  • Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module

    CN112824468A

  • Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module

    CN112898920A

  • Packaging adhesive film with high PID resistance and preparation method thereof

    CN113122164A

  • Ion barrier coating film as well as preparation method and application thereof

    CN115385580A